Analisis Implementasi Etika Bisnis Islam Pada Entitas Bisnis Furniture (Studi Kasus di CV Singgasana Benderang Abadi) - Mohamad Ainun Najib; Elif Pardiansyah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2022)
The purpose of this study is to explore the extent to which CV SBA implements business ethics in Islam. This is inseparable from the various issues that have developed that many SME business actors treat their employees arbitrarily, exploitatively and tyrannically. This prompted the author to conduct research at CV SBA as a furniture company located in South Tangerang City. The method used in this research is descriptive qualitative research. namely the work steps to describe an object, phenomenon, or social setting. Business ethics in this study uses the principles of Islamic business ethics proposed by Fauroni (2022), namely: 1) the principle of unity, 2) the principle of balance (tawazzun), 3) the principle of free will, 4) the principle of responsibility, and 5) the principle of truth (benevolence and honesty). CV SBA has run its business in accordance with Islamic business ethics. This refers to the 3 principles of Islamic business ethics that have been implemented in its business activities and activities. The principle of tauhin, the principle of fairness, and the principle of responsibility